2012
DOI: 10.1128/mcb.06444-11
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine-Regulated Translation of Spermidine/Spermine-N1-Acetyltransferase

Abstract: Rapid synthesis of the polyamine catabolic enzyme spermidine/spermine-N 1 -acetyltransferase (SSAT) in response to increased polyamines is an important polyamine homeostatic mechanism. Indirect evidence has suggested that there is an important control mechanism involving the release of a translational repressor protein that allows the immediate initiation of SSAT protein synthesis without RNA transcription, maturation, or translocation. To identify a repressor protein, we used a mass spectroscopy-based RNA-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 66 publications
1
44
0
Order By: Relevance
“…Similar polyamine N-acetyltransferases have been described in bacteria, e.g. SpeG acetylates spermidine in E. coli (Limsuwun and Jones, 2000), BltD (Woolridge et al, 1999) and PaiA (Forouhar et al, 2005) acetylate spermidine and spermine in Bacillus subtilis, spermidine and diamine acetyltransferase in the yeast Candida boidinii (Haywood and Large, 1985), and spermidine/spermine-N1-acetyltransferase in human (Perez-Leal et al, 2012). It is believed that cells typically adjust intracellular polyamine concentrations by acetylation in adaptation to stress (Carper et al, 1991;Casero and Pegg, 1993).…”
Section: Discussionmentioning
confidence: 79%
“…Similar polyamine N-acetyltransferases have been described in bacteria, e.g. SpeG acetylates spermidine in E. coli (Limsuwun and Jones, 2000), BltD (Woolridge et al, 1999) and PaiA (Forouhar et al, 2005) acetylate spermidine and spermine in Bacillus subtilis, spermidine and diamine acetyltransferase in the yeast Candida boidinii (Haywood and Large, 1985), and spermidine/spermine-N1-acetyltransferase in human (Perez-Leal et al, 2012). It is believed that cells typically adjust intracellular polyamine concentrations by acetylation in adaptation to stress (Carper et al, 1991;Casero and Pegg, 1993).…”
Section: Discussionmentioning
confidence: 79%
“…hSSAT-1 is a dimer or tetramer of ϳ65-80 kDa, with a subunit size of 20 kDa; contains 171 amino acids; and expresses a single 1.3-kb transcript (18). SSAT genes from mouse, rat, and hamster share regions of extensive similarity, including extensive 5Ј-and 3Ј-untranslated regions and a 200 -300-nucleotide poly(A) tail (19). The catalytic active site contains eight arginine residues, five of which have been implicated in acetyl-CoA binding (18).…”
Section: Discussionmentioning
confidence: 99%
“…Polyamine binding at this site may prevent protease attack and stabilize the protein (21), making it a good candidate for the amine substrate binding of the active site. Evidence from both human and mouse SSATs indicates a TATA-less promoter, a consensus sequences for a cAMP-responsive element at Ϫ487 bp, and several putative cisacting transcriptional elements (19). CpSSAT exhibits different kinetic characteristics compared with the host enzyme but is also found to be a homotetramer of 18 kDa, with arginine-rich motifs that are responsible for acetyl-CoA binding (4).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study using a human embryonic kidney cell line revealed these uORFs were able to repress SSAT translation [99]. In addition, the initiation region of SSAT mRNA contains a stem loop which is stabilized by a specific isoform of a protein called nucleolin [99].…”
Section: Controlling Pa Levels Through Catabolismmentioning
confidence: 99%
“…In addition, the initiation region of SSAT mRNA contains a stem loop which is stabilized by a specific isoform of a protein called nucleolin [99]. This interaction subsequently results in SSAT translation repression ( Fig 5A).…”
Section: Controlling Pa Levels Through Catabolismmentioning
confidence: 99%